Practical use of DAT SPECT imaging in diagnosing dementia with Lewy bodies: a US perspective of current guidelines and future directions - O’Shea, Deirdre M.; Arkhipenko, Alexander; Galasko, Douglas; Goldman, Jennifer G.; Sheikh, Zulfiqar Haider; Petrides, George; Toledo, Jon B.; Galvin, James E. (Frontiers in Neurology, 2024)
Background: Diagnosing Dementia with Lewy Bodies (DLB) remains a challenge in clinical practice. The use of 123 I-ioflupane (DaTscan TM ) SPECT imaging, which detects reduced dopamine transporter (DAT) uptake-a key biomarker in DLB diagnosis-could improve diagnostic accuracy. However, DAT imaging is underutilized despite its potential, contributing to delays and suboptimal patient management. Methods: This review evaluates DLB diagnostic practices and challenges faced within the U.S. by synthesizing information from current literature, consensus guidelines, expert opinions, and recent updates on DaTscan FDA filings. It contrasts DAT SPECT with alternative biomarkers, provides recommendations for when DAT SPECT imaging may be indicated and discusses the potential of emerging biomarkers in enhancing diagnostic approaches. Results: The radiopharmaceutical 123 I-ioflupane for SPECT imaging was initially approved in Europe (2000) and later in the US (2011) for Parkinsonism/Essential Tremor. Its application was extended in 2022 to include the diagnosis of DLB. DaTscan's diagnostic efficacy for DLB, with its sensitivity, specificity, and predictive values, confirms its clinical utility. However, US implementation faces challenges such as insurance barriers, costs, access issues, and regional availability disparities. Conclusions: 123 I-ioflupane SPECT Imaging is indicated for DLB diagnosis and differential diagnosis of Alzheimer's Disease, particularly in uncertain cases. Addressing diagnostic obstacles and enhancing physician-patient education could improve and expedite DLB diagnosis.Collaborative efforts among neurologists, geriatric psychiatrists, psychologists, and memory clinic staff are key to increasing diagnostic accuracy and care in DLB management.